Effects of Supplementing Corn Silage to Fall-Calving Heifers and Cows Grazing Bermudagrass and Calf Performance and Physiology - J. Wyatt L. Banks; Jaymelynn K. Farney; Karol E. Fike; Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2024)
The objective was to test the effect of supplemental feeding on cows grazing bermudagrass pastures on cow-calf performance and pasture management. In a completely randomized design, (n = 24) primiparous and multiparous Angus-based cross cows were allocated to bermudagrass pasture with one of two levels of supplemental feeding (non-supplemented or supplemented at 1% of BW on a DM basis of corn silage). Each treatment consisted of (n = 4) pastures stocked with three cows of different ages, a young (first-calf heifer), middle-aged (3-5 yrs.), and old (≥ 6 yrs.) cow, each averaging 155 ± 14 d of gestation at turnout. Cows were fed silage (32-42% DM and 7.83% CP) daily in fence-line bunks, with feeding amount being adjusted at each weigh date. Cows were weighed on 2 consecutive days prior to turnout (middle of the second trimester), midpoint (beginning of the third trimester), and at about 2 weeks prior to the estimated calving date for the herd. Body weight, body condition score, hair score, hair length, and rump fat measurements were taken at each weigh date. Following the final measurement day, cows were relocated to calving pastures consisting of a mixture of bermudagrass, tall fescue, and prairie grass. Supplemental feeding of late gestation fall-calving cows on bermudagrass pasture did not have an effect on cow-calf performance, calf birth weights, and milk output. However, supplemental feeding of cows with corn silage during the summer resulted in 31% more available forage in the pastures. Overall, there were minimal differences in cow performance while grazing bermudagrass pastures during the summer and with supplemental feeding of corn silage. The greatest advantage comes from a greater amount of forage available, which may offset periods of drought or allow producers to increase stocking rates on their property.
Keywords: bermudagrass; cow-calf; silage